Peningkatan keterampilan berbicara siswa kelas IV melalui model snowball throwing UPTD SD Negeri 6 Gandapura - jasmaniar; Nurlaili; Muhammad Darwis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve the speaking skills of fourth-grade students through the implementation of the Snowball Throwing learning model at UPTD SD Negeri 6 Gandapura. The study was motivated by the low speaking ability of students, which was indicated by a lack of confidence, unclear voice delivery, and difficulty in expressing ideas orally. This research employed a qualitative approach with the type of Classroom Action Research conducted in two cycles. The subjects of this study were 23 fourth-grade students. Data were collected through tests, observations, and interviews. The results showed that the implementation of the Snowball Throwing learning model was able to improve students’ speaking skills. In the first cycle, the percentage of students’ learning completeness reached 65.21%, and it increased in the second cycle until it achieved the expected classical completeness target. The activities of both teachers and students during the learning process were categorized as very good. Students became more active, confident, and enthusiastic in participating in learning activities. Interview results showed that students felt happy and more confident when learning through the Snowball Throwing model. Based on the findings, it can be concluded that the Snowball Throwing learning model can improve the speaking skills of fourth-grade students at UPTD SD Negeri 6 Gandapura.